Pengaruh Struktur Modal, Ukuran Perusahaan, Kebijakan Dividen, Kepemilikan Manajerial dan Kepemilikan Institusional terhadap Nilai Perusahaan Barang Konsumen Primer yang Terdaftar di BEI Periode 2018-2022 - Audiva Paramitha Oktadiani; Muhamad Syaichu (Diponegoro Journal of Management, 2025)
Several previous studies that examined the factors that influence company value showed a gap in research results. This study aims to analyze the effect of capital structure, firm size, dividend policy, managerial ownership, and institutional ownership on firm value. PBV is used as a proxy for firm value, while the independent variables used in this study include capital structure, firm size, dividend policy, managerial ownership, and institutional ownership.The population used in this study is consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022 and through the purposive sampling method, the samples selected in this study were 38 companies. This research was conducted using quantitative data methods and analyzed using panel data regression analysis methods with the selected estimation model in this study, namely the Fixed Effect Model (FEM) through the E-views 13 program.The results of the analysis of this study indicate that capital structure and institutional ownership have a positive and insignificant effect on firm value, while dividend policy and firm size have a significant negative effect on firm value. This study found a significant positive effect of managerial ownership on firm value.